Math, asked by rajaditi919, 4 months ago

rationalise
1+√2/2-√2​

Answers

Answered by StormEyes
4

Solution!!

\sf \dfrac{1+\sqrt{2}}{2-\sqrt{2}}

Multiply the fraction by \sf \dfrac{2+\sqrt{2}}{2+\sqrt{2}}.

\sf =\dfrac{1+\sqrt{2}}{2-\sqrt{2}}\times \dfrac{2+\sqrt{2}}{2+\sqrt{2}}

To multiply the fractions, multiply the numerator and denominator separately.

\sf =\dfrac{(1+\sqrt{2})(2+\sqrt{2})}{(2-\sqrt{2})(2+\sqrt{2})}

Multiply the parentheses.

\sf =\dfrac{2+\sqrt{2}+2\sqrt{2}+2}{(2-\sqrt{2})(2+\sqrt{2})}

Use (a - b)(a + b) = a² - b² to simplify the product in the denominator.

\sf =\dfrac{2+\sqrt{2}+2\sqrt{2}+2}{(2)^{2}-(\sqrt{2})^{2}}

\sf =\dfrac{2+\sqrt{2}+2\sqrt{2}+2}{4-2}

Add the numbers in the numerator.

\sf =\dfrac{4+\sqrt{2}+2\sqrt{2}}{4-2}

Collect the like terms in the numerator.

\sf =\dfrac{4+3\sqrt{2}}{4-2}

Subtract the numbers in the denominator.

\sf =\dfrac{4+3\sqrt{2}}{2}

Similar questions